On fire : the 7 choices to ignite a radically inspired life - O'Leary, John, 1977-; DiTiberio, Cynthia (North Star Way, 2016)
"If you could go back in time, would you do it all again? When John O'Leary was just nine years old, he barely survived a devastating house fire with burns on 100 percent of his body. O'Leary's doctors told his parents that he wasn't expected to make it through the night. But this story didn't end there. O'Leary, bolstered by several extraordinary people in his life, made it through five months of healing in the hospital, and then through the years of excruciating rehabilitation that followed as he struggled to regain mobility and control of his body. The insights he gained through this experience profoundly changed his life, but today John says that it actually changed him for the better--and that if he had it to do all over again, he wouldn't change a thing. How is this possible? What makes some people crumble in the face of adversity while others thrive? What are the secrets each of us can glean from John's extraordinary story of resilience? An honest and incredible account of triumph over tragedy, On Fire contains O'Leary's reflections on the seven life-giving choices he made that ensured his survival and his ability to ignite a radically inspired life. On Fire encourages us to seize the power to transform our lives from ordinary to extraordinary, no matter what our circumstances. As O'Leary says, 'You can't always choose the path that you walk in life, but you can always choose the manner in which you walk it.' Once expected to die, John O'Leary now teaches others how to truly live."--Dust jacket.